The Impact of Gender Inequality and Economic Variables on Education Inequality: Panel Data Analysis - Sugeng Setyadi (Gorontalo Development Review, 2022)
Education plays a central role and becomes one of the goals of sustainable development which must continuously be carried out equitably and can be accessed by anyone without any limitations on geographical conditions or social and economic status. However, the issue of education inequality has recently become a worrying concern, therefore the purpose of this study is to analyze the factors that influence education inequality in the Regency or City of East Java Province where the education inequality is the highest on the island of Java. The data used in this study is secondary data sourced from the Central Statistics Agency and the Ministry of Education. The analytical method used is panel data regression. The results showed that per capita GRDP, literacy rate, government spending in the education sector and gender inequality had an effect on educational inequality. So that government policies are needed that are able to build public awareness of the importance of investment in the field of human capital, and the role of education for women and men in achieving a better quality of life, as well as the need for policy reforms in placing government expenditure allocations for education that are more targeted.